2013
DOI: 10.1155/2013/391085
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Close Follow-Up in the Fetus with Premature Atrial Contractions Accompanied by Atrial Septal Aneurysm: A Case Report

Abstract: Rhythms that derive from parts of atria other than the sinus node are called premature atrial contractions (PACs). Vast majority of fetal PACs are idiopathic. Fetal PACs usually have a good prognosis and disappear spontaneously during pregnancy or after delivery. Development of fetal tachycardia or fetal bradycardia is rarely reported during follow-up of fetuses diagnosed with PACs. To the best of our knowledge, coexistence of tachycardia and bradycardia leading to hemodynamic impairment has not yet been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In fetuses, the cut-off point for diagnosis of excessive excursion is defined as greater than 1.3 MoM or an excursion ratio of greater than 55% [ 23 ], whereas some authors use a cut-off of 50% [ 6 ]. As mentioned earlier, ASA may be associated with dysrhythmias, especially, premature atrial contractions (PACs), which is the most common type of arrhythmias reported to be secondary to ASA [ 10 , 24 ]. Fetal PACs usually have a good prognosis and disappear spontaneously during pregnancy or shortly after birth [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fetuses, the cut-off point for diagnosis of excessive excursion is defined as greater than 1.3 MoM or an excursion ratio of greater than 55% [ 23 ], whereas some authors use a cut-off of 50% [ 6 ]. As mentioned earlier, ASA may be associated with dysrhythmias, especially, premature atrial contractions (PACs), which is the most common type of arrhythmias reported to be secondary to ASA [ 10 , 24 ]. Fetal PACs usually have a good prognosis and disappear spontaneously during pregnancy or shortly after birth [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coarctation of the aorta was also sometimes observed alongside ASA, but there is no known association between these two conditions [ 1 ]. ASA-associated arrhythmias consist mostly of premature atrial contractions (PAC), which can sometimes progress to supraventricular tachycardia [ 5 , 6 , 7 ]. If the foramen ovale flap is very redundant, it can make a cyclical contact with the mitral valve and even protrude in the LV, thus obstructing its inflow.…”
mentioning
confidence: 99%